Implementasi Perangkat Pembelajaran Fisika Berbasis Pembelajaran Inkuiri dengan Strategi Konflik Kognitif untuk Melatihkan Kemampuan Berpikir Kritis - Asy’ari, Muhammad (Lensa : Jurnal Kependidikan Fisika, 2017)
[Title: Implementation of Physics Learning Tools Based on Inquiry Learning with Conflict Cognitive Strategies to Facilitate Critical Thinking Ability]. This study aims to implement physics learning device based on inquiry with conflict cognitive strategy to facilitate student’s critical thinking on the fluid material. The device is implemented in the first semester students of Physics Education Study Program IKIP Mataram academic year 2017/2018 with test design using one group pre-test post-test design. Data collection methods used were questionnaires, tests, and observations, while data analysis techniques used qualitative and quantitative descriptive analysis. The results of the implementation obtained some findings, namely: learning activities can be done well with the high degree of reliability. Student response to learning is very positive with the interest of students to follow the learning. The students' critical thinking skills after the experimentally developed learning tools are critically developed. Based on the results of this study can be concluded that learning tools that are implemented practical, and effectively used to facilitate students' critical thinking skills.